Analysis of Key Entrepreneurial Success Factors in Tilapia Hatchery Businesses - Harmain, Ummu; Purwansyah, Jaka Karona Indra (Journal of Supply Chain and Entrepreneurship, 2025)
Aim: This study explores the key factors influencing the success of tilapia hatchery businesses in Nagori Wonorejo, with a particular focus on social capital and social media utilization. By understanding these factors, the research aims to provide insights into effective strategies that can enhance business sustainability and competitiveness in the aquaculture sector.Method: A quantitative research design was applied, utilizing multiple linear regression analysis to assess the relationship between social capital, social media utilization, and business success. Data were obtained through structured questionnaires distributed to tilapia hatchery entrepreneurs. To ensure reliability and validity, statistical evaluations, including validity tests, reliability assessments, and hypothesis testing, were conducted using appropriate analytical tools.Findings: The results indicate that social capital does not have a significant partial effect on business success, likely due to the fluctuating nature of social interactions, which makes its influence inconsistent. However, social media utilization plays a crucial role, significantly contributing to business expansion through digital marketing, customer interactions, and network development. When examined collectively, social capital and social media utilization together influence business performance, suggesting that while social capital alone may not drive success, its combination with digital strategies enhances efficiency and market reach.Significance: These findings emphasize the increasing importance of digital adaptation in aquaculture businesses, demonstrating that entrepreneurs who effectively integrate digital tools with strong business relationships have a greater likelihood of achieving long-term stability and competitive advantage. This study provides practical insights for policymakers, financial institutions, and industry stakeholders in developing supportive policies, funding opportunities, and training programs to strengthen the resilience and growth of small-scale hatchery businesses.